Prevalence of self-medication practice with herbal products among non-psychotic psychiatric patients from southeastern Serbia: A cross-sectional study - Nikola M. Stojanović; Ljiljana Samardžić; Pavle J. Randjelović; Niko S. Radulović (Elsevier, 2017)
The aim of this study was to evaluate the usage prevalence of herbal products (HP) and to ascertain the identity, mode and adverse effects of plant taxa used in self-medication practice for anxiety, depression and insomnia in patients with non-psychotic disorders originating from southeastern Serbia. Also, we compared HP users and non-users on the variables of socio-demographic characteristics, information source and origin of HP. The study was done by a face-to-face interview with a trained psychiatrist using a structured questionnaire administered to 136 adult patients suffering from non-psychotic mental disorders. A typical herbal-product user among non-psychotic psychiatric patients from southeastern Serbia is a middle-aged married woman, with a secondary level of education, unemployed and living in an urban area. Non-psychotic psychiatric patients, although not living predominantly in rural areas, were familiar with a variety of ethno-medicines and were often using HP primarily without the consultation of their psychiatrists/physicians. HP stated to be most frequently used for psychiatry-related symptoms included: Melissa officinalis, Mentha × piperita, Hypericum perforatum and Valeriana officinalis. The interviewees rarely stated adverse reactions related to the HP usage; however, this should not be generalized, since HP are known to vary in the content of their adverse reaction-causing constituents.